Metabolic enhancement of 2, 3′, 4, 4′, 5-pentachlorobiphenyl (CB118) using cytochrome P450 monooxygenase isolated from soil bacterium under the presence of perfluorocarboxylic acids (PFCAs) and the structural basis of its metabolism. (November 2018) - Goto, Erika; Haga, Yuki; Kubo, Makoto; Itoh, Toshimasa; Kasai, Chie; Shoji, Osami; Yamamoto, Keiko; Matsumura, Chisato; Nakano, Takeshi; Inui, Hideyuki
Abstract: 2, 3′, 4, 4′, 5-Pentachlorobiphenyl (CB118) is one of the most abundant polychlorinated biphenyl (PCB) congeners in the environment, and perfluoroalkyl acids, including perfluorocarboxylic acids (PFCAs), are widely distributed in the environment. Although CB118 and perfluoroalkyl acids are present in all humans and biota, effects in the metabolic fate of CB118 leading to toxicity change are unclear. P450BM3, which is isolated from the soil bacterium Bacillus megaterium, metabolized CB118 to three different hydroxylated pentachlorobiphenyls (M1-M3). M2 was identified as 4′-OH-2, 3′, 4, 5, 5′-pentachlorobiphenyl. These reactions were promoted by the presence of PFCAs, and perfluorooctanoic acid (PFCA-C8) was the most effective for accelerating these reactions among PFCAs with different carbon chain length. The production rate of M2 was accelerated by 25-times using PFCA-C8. Furthermore, the docking models of P450BM3 with CB118 and PFCAs revealed that the conformational changes of the substrate-binding cavity of P450BM3 after binding of PFCAs to P450BM3 were important for selective production of CB118 metabolites. This study leads to the clarification of the different metabolic fates of PCBs under complex contamination with PFCAs. Graphical abstract: Image 1 Highlights: Bacterial P450BM3 metabolized CB118 to hydroxylated metabolites. Hydroxylation of CB118 was promoted by the existence of PFCAs. The size of the substrate-binding cavity of P450BM3 was changed by binding PFCAs. Metabolic fates of PCBs under complex contamination with PFCAs may be different.